PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA MAKASSAR - Ardiansyah Halim (Universitas Bina Taruna Gorontalo, 2020)
The purpose of this study was to determine and analyze the influence of leadership style (X) consisting of supportive leadership (X1), directive leadership (X2), participative leadership (X3) both simultaneously and partially on employee performance (Y) at Departement of Education and Culture of Makassar City. This type of research is a quantitative descriptive study. The nature of this research is explanatory research. The population in this study were employees on the Departement of Education and Culture of Makassar City, totaling 58 civil servants. The reason was that the number of civil servants was small so the entire population was sampled in this study (census). Data collection techniques in this study were carried out through interviews, questionnaires, and documentation studies. The results showed that simultaneously there is a positive and significant influence of leadership style on employee performance. Partially supportive (X1) and participatory (X3) leadership style variables have a positive and significant effect on employee performance, while directive leadership style (X2) has no significant effect on Departement of Education and Culture of Makassar City.